Implementation of Regional Regulation Policy on The Sustainability of The Ammatoa Kajang Customary Forest - Andi Ahmad Malikul Afdal (IHSA Institute, 2022)
The policy that preserves the Kajang customary forest through regional regulation (PERDA No. 9 of 2015) concerning the strengthening and the protection of the rights towards the Ammatoa customary forest community in orders and authorities of the Ammatoa Kajang customary law community, namely to fulfill, maintain, and perpetuate “Pasang” as a guideline for the order of community life. Thus, through this qualitative descriptive study, it attempts to describe how policy implementation is related to the George C. Edward III implementation model and then analyzes it to an absolute conclusion. The results showed that the implementation of the regional regulation in preserving the Ammatoa customary law in the Kajang indigenous people based on four indicators, namely: communication, resources, disposition and bureaucratic structure had been well. However, it cannot be denied that in the implementation of PERDA No. 9 of 2015 there are still many shortcomings in it.